Rancangan Gim Visual Novel “GO VEGETARIAN” Untuk Edukasi Pola Hidup Sehat - Anthonius; Simalango, Holong Marisi (Fakultas Komputer - Universitas Universal, 2024)
A vegetarian diet is a pattern that avoids meat consumption and increases the intake of plant-based foods, which has attracted public interest with claims of its health benefits. Starting a vegetarian diet correctly and ensuring adequate nutritional information is a challenge for beginners. Very few outreach media still suit young people's needs in visual form. This research aims to design and build an Android-based visual novel game as an easy-to-understand educational medium about the vegetarian lifestyle. Game development applies the Game Development Life Cycle (GDLC) section and beta testing using data collection techniques through questionnaires. The application was made using Unity Engine version 2020. The results of the research through the creation of a visual novel game showed that the results of a questionnaire were obtained where 66.7% of respondents answered that they were very motivated to become vegetarian and 57.6% responded that they were very interested in adopting a vegetarian lifestyle.